Sorghum farmers’ perceptions of climate change, its effects, temperature and precipitation trends, and determinants of adaptation strategies in the central plateau zone of Rwanda - Theogene Niyibigira; Wassu Mohammed; Tamado Tana; Tesfaye Lemma Tefera; Placide Rukundo (Cogent Food & Agriculture)
Climate change is causing significant damage to crop production in the central plateau zone of Rwanda, particularly affecting sorghum, food, and the incomes of smallholder farmers. Understanding farmers’ perceptions and the factors impacting their responses is crucial for improving sorghum production policies and programs. Therefore, a study was conducted to assess sorghum farmers’ perceptions of climate change and the factors determining their adaptation strategies. A multistage sampling method and a cluster random selection were utilized to select 345 respondents from five districts of the study area. The data were analyzed using descriptive statistics and a multivariate probit model. The results showed that 98.8% of farmers were aware of climate change, with deforestation being the main anthropogenic activity causing it. Consequently, 95.7% and 84.3% of farmers experienced grain yield reductions, and over 20 sorghum varieties disappeared. To address these impacts, farmers adopted five adaptation strategies: early maturing sorghum varieties (67%), adjusting planting dates (50.1%), drought-tolerant varieties (46.7%), soil conservation practices (38.3%), and crop diversification (32.8%). The multivariate probit model results showed the age and literacy level of the household head, access to extension services, access to information, access to credit, farming experience, and land size as the important factors influencing at least one of the climate change adaptation strategies. The study concluded that sorghum farmers are aware of the impacts of climate change and are acting to address its negative effects. The results suggest that the government and stakeholders should support farmers in strengthening their adaptation strategies for sustainable sorghum production.